2017
DOI: 10.1371/journal.pone.0175844
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional networks are associated with resistance to Mycobacterium tuberculosis infection

Abstract: RationaleUnderstanding mechanisms of resistance to M. tuberculosis (M.tb) infection in humans could identify novel therapeutic strategies as it has for other infectious diseases, such as HIV.ObjectivesTo compare the early transcriptional response of M.tb-infected monocytes between Ugandan household contacts of tuberculosis patients who demonstrate clinical resistance to M.tb infection (cases) and matched controls with latent tuberculosis infection.MethodsCases (n = 10) and controls (n = 18) were selected from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(67 citation statements)
references
References 38 publications
2
65
0
Order By: Relevance
“…Deletion of IFNAR1 (interferon alpha and beta receptor subunit 1) in the type I interferon signaling pathway can increase resistance to Mtb in mice (Mayer-Barber et al, 2014), and a proline deletion in IFNAR1 increases resistance to TB in some human populations (Zhang et al, 2018). HDAC (histone deacetylase) regulates the pro-inflammatory response of host cells, and HDAC inhibition restricts intracellular Mtb growth (Seshadri et al, 2017). PDE (phosphodiesterase) inhibitors improve the clearance of Mtb in rabbit lungs, restrict Mtb growth, and increase mouse survival (Maiga et al, 2012; Subbian et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…Deletion of IFNAR1 (interferon alpha and beta receptor subunit 1) in the type I interferon signaling pathway can increase resistance to Mtb in mice (Mayer-Barber et al, 2014), and a proline deletion in IFNAR1 increases resistance to TB in some human populations (Zhang et al, 2018). HDAC (histone deacetylase) regulates the pro-inflammatory response of host cells, and HDAC inhibition restricts intracellular Mtb growth (Seshadri et al, 2017). PDE (phosphodiesterase) inhibitors improve the clearance of Mtb in rabbit lungs, restrict Mtb growth, and increase mouse survival (Maiga et al, 2012; Subbian et al, 2011).…”
Section: Resultsmentioning
confidence: 99%
“…We identified a locus near IL12B , a previously described candidate gene that has been shown to affect response to TB in mice as well as define highly susceptible families that have an IL12B knockout as well as among persons with MSMD. We have also studied persistently tuberculin skin test negativity despite close and prolonged exposure to active TB cases [64, 65] – while the focus here is on infection and not disease, this resistance phenotype may help identify novel targets for vaccine development and host directed therapies [66]. …”
Section: Resistance Vs Susceptibility As a Measured Phenotypementioning
confidence: 99%
“…Gene expression studies indicated that the sodium butyrate pathway was associated with persistent TST negativity. Follow-up studies demonstrated that sodium butyrate and histone deacetylase inhibitors were associated with immunological response to MTB in vitro [66]. While these studies had smaller sample sizes, they often included independent case-control replication sets with functional validation relevant to TB biology.…”
Section: Necessary Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Transcriptomics has proven less powerful in differentiating healthy controls from LTBI patients although recent transcriptomics studies identified histone deacetylation as a key event in Mtb infection resistance in monocytes (24). Unfortunately, there is no gold-standard for identifying LTBI patients who are truly infected with Mtb since we cannot distinguish a possible anamnestic response to Mtb antigens from persistent infection.…”
Section: Infection With Mtbmentioning
confidence: 99%